2005
DOI: 10.1007/s00248-003-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

Links between Phytoplankton and Bacterial Community Dynamics in a Coastal Marine Environment

Abstract: Bacteria and phytoplankton dynamics are thought to be closely linked in coastal marine environments, with correlations frequently observed between bacterial and phytoplankton biomass. In contrast, little is known about how these communities interact with each other at the species composition level. The purpose of the current study was to analyze bacterial community dynamics in a productive, coastal ecosystem and to determine whether they were related to phytoplankton community dynamics. Near-surface seawater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
175
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(198 citation statements)
references
References 48 publications
16
175
0
7
Order By: Relevance
“…This method provides the possibility to identify the community members by reamplifying and sequencing of the excised bands. Previously, DGGE technique was successfully applied to reveal the alterations of bacterial or total microbial communities in freshwater and seawater habitats infl uenced by different environmental factors [10,11,12,13,14]. According to the UPGMA dendrogram based on the DGGE patterns, signifi cant seasonal changes with less spatial differences were found among the total planktonic bacterial communities of Lake Hévíz (Fig.…”
Section: Microbial Community Structuresmentioning
confidence: 99%
“…This method provides the possibility to identify the community members by reamplifying and sequencing of the excised bands. Previously, DGGE technique was successfully applied to reveal the alterations of bacterial or total microbial communities in freshwater and seawater habitats infl uenced by different environmental factors [10,11,12,13,14]. According to the UPGMA dendrogram based on the DGGE patterns, signifi cant seasonal changes with less spatial differences were found among the total planktonic bacterial communities of Lake Hévíz (Fig.…”
Section: Microbial Community Structuresmentioning
confidence: 99%
“…Still, recent advances provided a new look at an old topic: our understanding of DOC-bacteria interaction has moved from an extreme specialization view, where few specific bacterioplankton strains responded to a particular phytoplankton species (for example, González et al, 2000;Schafer et al, 2002;Pinhassi et al, 2004;Grossart et al, 2005;Rooney-Varga et al, 2005;Sapp et al, 2007a) to a more moderate (generalist) and complex view where many types of bacteria are involved in the decomposition of different types of DOCp with differences in their uptake rates (Nelson and Carlson, 2012;Sarmento and Gasol, 2012;Landa et al, 2013;Paver et al, 2013;Morana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular method-based studies have indicated that bacterial diversity in sediment has been linked with impacts of anthropogenic activities, such as increase of eutrophication and chemical pollution [9][10][11][12][13], changes in species of phytoplankton or zooplankton [14][15][16], and operating a dredging, reclamation, or remediation project [17][18][19][20]. Furthermore, some efforts have been made to study the bacterial community structure dynamics related to mariculture processes.…”
Section: Introductionmentioning
confidence: 99%